The development of cultural integrated Indonesian speaking e-module for higher education students in Indonesia - Munirah Munirah; Syahruddin Syahruddin; Akram Budiman Yusuf (Indonesian Journal of Applied Linguistics, 2023)
The importance of language proficiency, particularly speaking skill competence, has been acknowledged in the field of education for many years. However, despite numerous efforts to improve it, the achievement of student speaking skill competence is still far from the expected target. One of the main reasons behind this problem is the availability, accessibility, and validity of the teaching materials used. This study aimed to address the issue of unsatisfactory Indonesian students’ speaking abilities, which are partly attributed to the lack of available teaching media, particularly those that integrate cultural values. Therefore, this research used research and development study of a speaking skill e-module that is integrated with cultural values that was developed in an Android-based device. The module was designed for university students in South Sulawesi, Indonesia. The results of the study indicated that the use of the speaking e-module helped improve students' speaking abilities, as well as their understanding of cultural values. Therefore, this research is also expected to reach the potential to be beneficial to a wider audience in Indonesia, beyond the scope of South Sulawesi universities.